Objective Assessment of Anesthesiology Resident Skills Using an Innovative Competition-Based Simulation Approach. Issue 5 (1st September 2015) - Rebel, Annette; DiLorenzo, Amy; Fragneto, Regina Y.; Dority, Jeremy S.; Rose, Greg L.; Nguyen, Dung; Hassan, Zaki-Udin; Schell, Randall M.
Abstract : Residency programs are charged with teaching, assessing, and documenting resident competency for a multitude of skills. Documentation of competency requires demonstrating specific milestones mandated by the Accreditation Council for Graduate Medical Education. Our department designed an innovative, competition-based approach to objectively assess the skill level of postgraduate year 1 residents in performing basic anesthesia-related tasks after 1 month of anesthesiology training. We launched an "Olympic" event to assess requisite skills in an environment of friendly competition. A simulation format was chosen to allow standardized objective assessment of the resident's skill level at an early stage of training, with possible identification of and intervention for skills needing improvement. Our experience may serve as a template for other programs and specialties developing processes for assessing and documenting improvement in skill and competency over the course of residency training.